IS IT MANDATORY TO LIGATE SAC IN EMERGENCY HERNIOTOMY IN PEDIATRIC AGE GROUP? A PROSPECTIVE COHORT - Haj, Zainab; Shawana Asad; Zaheer Qureshi; Irfan ud Din Khattak (Journal of Ayub Medical College Abbottabad, 2022)
Background: Herniotomy is standard treatment for inguinal hernia in children. Paediatric surgeons remain divided on whether ligation of sac is mandatory. In our study, we left the sac open to see early recurrence. Methods: This quasi=experimental study, done in emergency cases, was sequel to our previous study done in elective cases. It was carried out at surgical unit C of Ayub Hospital Complex, Abbottabad, from Jan 2016 to June 2020. Children from birth to 12 years of age were randomly divided into two groups. In group I (experimental), sacs were cut high up and left open during herniotomy while in group II (control), high ligation of hernia sac was done. Follow up was scheduled for day 10 and 1, 3 and 6 months. Patients were assessed for early recurrence and other complications. Results: A total of 151 emergency inguinal herniotomies were done including 147 males (97.4%) and 4 females (2.6%). 136 sacs (90.1%) were ligated with vicryl 3/0 or 4/0 while 15 sacs (9.9%) were left open. We did not find early recurrence, but found 1 case of scrotal hematoma (n=1/15) (6.7%) and 1 case of scrotal oedema (n=1/15) (6.7%) in the experimental group. In control group, complications were similar with 7 cases of hematoma (n=7/136) (5.1%) and 9 cases of scrotal oedema (n=9/136) (6.6%). Conclusion: Complications are comparable in herniotomy with or without ligation of sac but ligation adds an extra step. Herniotomy without sac ligation in children is safe and preferable in emergency setup.